External Debt, Exchange Rate, and Unemployment in Selected ASEAN Countries - Cahyadin, Malik; Ratwianingsih, Lely (Universitas Muhammadiyah Yogyakarta, 2020)
This research examines the empirical model of external debt, exchange rate, and unemployment in selected ASEAN Countries during 1980-2017. The countries included Indonesia, Malaysia, Thailand and the Philippines. The data were collected from the World Bank publications. The ARDL-ECM and Granger Causality Test (GCT) were employed to address the research objectives. The findings indicated that there were short-term effects on each empirical model (external debt, exchange rate, and unemployment). Furthermore, the stability test exhibited that the models were precise and stable. The GCT result showed that there was a causal between external debt, exchange rate, and unemployment, especially in Indonesia. Moreover, the linkages between external debt, exchange rate, and unemployment in selected ASEAN Countries were co-movement. Therefore, the governments are expected to emphasis on macroeconomic policies, such as pro-stability of the exchange rate, external debt risk management, and pro-poor.